MANAGING HIGH-END, HIGH-VOLUME INNOVATIVE PRODUCTS - Gembong Baskoro (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2008)
This paper discuses the concept of managing high-end, high-volume innovative products. High-end, high-volume consumer products are products that have considerable influence to the way of life. Characteristic of High-end, high-volume consumer products are (1) short cycle time, (2) quick obsolete time, and (3) rapid price erosion. Beside the disadvantages that they are high risk for manufacturers, if manufacturers are able to understand precisely the consumer needs then they have the potential benefit or success to be the market leader. High innovation implies to high utilization of the user, therefore these products can influence indirectly to the way of people life. The objective of managing them is to achieve sustainability of the products development and innovation. This paper observes the behavior of these products in companies operated in high-end, high-volume consumer product.